2023
DOI: 10.1177/10781552231158744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biliary toxicity in patients with hepatic artery infusion pumps

Abstract: Purpose Identify risk factors for biliary toxicity in patients with colorectal liver metastases who received floxuridine (FUDR) via a surgically implanted hepatic artery infusion pump (HAIP). Describe the incidence of biliary toxicity and evaluate relevant patterns in the biliary toxicity cohort. Methods A single center, retrospective, case-control study included adult colorectal cancer patients with liver metastases who received at least one cycle of FUDR via a surgically implanted HAIP from 1 January 2017, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The authors noted that the risk factors for BS were postoperative infectious complications (50.0% vs. 14.8%, p = 0.002) and larger dose/cycle/weight of FUDR (2.6 vs. 2.0 mg/cycle/kg, p = 0.025); they also noted that the development of BS did not negatively impact survival in these patients (BS vs. non-BS: 61.0 months vs. 47.2 months, p = 0.316). Additionally, prior studies have demonstrated that biliary toxicity from HAIP can be limited by the concomitant administration of dexamethasone with FUDR [ 131 ] and that an increase in alkaline phosphatase (ALP) may be an early indicator of toxicity [ 132 ]. As such, frequent lab monitoring can be used for surveillance purposes, and dose adjustments or treatment breaks have been shown to limit BS development [ 133 ].…”
Section: Perioperative Considerationsmentioning
confidence: 99%
“…The authors noted that the risk factors for BS were postoperative infectious complications (50.0% vs. 14.8%, p = 0.002) and larger dose/cycle/weight of FUDR (2.6 vs. 2.0 mg/cycle/kg, p = 0.025); they also noted that the development of BS did not negatively impact survival in these patients (BS vs. non-BS: 61.0 months vs. 47.2 months, p = 0.316). Additionally, prior studies have demonstrated that biliary toxicity from HAIP can be limited by the concomitant administration of dexamethasone with FUDR [ 131 ] and that an increase in alkaline phosphatase (ALP) may be an early indicator of toxicity [ 132 ]. As such, frequent lab monitoring can be used for surveillance purposes, and dose adjustments or treatment breaks have been shown to limit BS development [ 133 ].…”
Section: Perioperative Considerationsmentioning
confidence: 99%